Joseph de Maistre and the legacy of Enlightenment - Armenteros, C (Voltaire Foundation, 2017)
Although Joseph de Maistre has long been regarded as characterising the Counter-Enlightenment, his intellectual relationship to eighteenth-century philosophy remains unexplored. In this first comprehensive assessment of Joseph de Maistre’s response to the Enlightenment, a team of renowned scholars uncover a writer who was both the foe and heir of the philosophes. While Maistre was deeply indebted to thinkers who helped to fashion the Enlightenment – Rousseau, the Cambridge Platonists – he also agreed with philosophers such as Schopenhauer who adopted an overtly critical stance. His idea of genius, his critique of America and his historical theory all used ‘enlightened’ language to contradict Enlightenment principles. Most intriguingly, and completely unsuspected until now, Maistre used the writings of the early Christian theologian Origen to develop a new, late, religious form of Enlightenment that shattered the logic of philosophie. The Joseph de Maistre revealed in this book calls into question any simple opposition of Enlightenment and Counter-Enlightenment, and offers particular lessons for our own time, when religion is at the forefront of public debate and a powerful political tool. Carolina Armenteros and Richard A. Lebrun, Introduction I. Polemics of the Counter-Enlightenment Darrin M. McMahon, The genius of Maistre Joseph Eaton, ‘This babe-in-arms’: Joseph de Maistre’s critique of America Jean-Yves Pranchère, The negative of the Enlightenment, the positive of order and the impossible positivity of history II. Makers and heirs of the Enlightenment Philippe Barthelet, The Cambridge Platonists mirrored by Joseph de Maistre Carolina Armenteros, Maistre’s Rousseaus Yannis Constantinidès, Two great enemies of the Enlightenment: Joseph de Maistre and Schopenhauer III. Maistrian afterlives of the theological Enlightenment Douglas Hedley, Enigmatic images of an invisible world: sacrifice, suffering and theodicy in Joseph de Maistre Emile Perreau-Saussine, Why Maistre became Ultramontane Aimee E. Barbeau, The Savoyard philosopher: deist or Neoplatonist? Elcio Vercosa Filho, The pedagogical nature of Maistre’s thought Carolina Armenteros, Conclusion Summaries Bibliography Index